Value Tilt Test Sensitized with Isosorbide Dinitrate Sublingual 5 mg in Patients with Recurrent Syncope Departure Not Determined - Yanac, Pedro (1998)
OBJECTIVE : Sign in our study of recurrent syncope of undetermined origin employing Tilt Test (PI) sensitized with isosorbide dinitrate (ISB) . MATERIAL AND METHODS : Prospective study of patients with recurrent syncope , hedge 1995 - 1996 hedge at the Naval Medical Center , using the PI (80° for 25 min) . If you tested negative , was repeated but with ISB 5 mg SL. The same protocol was performed in patients without a history of syncope. RESULTS : 23 patients were studied. In the baseline test , 4 (17%) tested positive , at 19 (83%) were negative ISB stimulated with 5 mg SL : 10 patients had positive response (43% of total). Only one patient had side effects ( severe headache) . Only one control subject (8 %) had PI (+) after the administration of ISB. Most patients (64 %) were under 40 years. The frequency of positive tests going and specificity of the test with ISU SL is 60 % and 92 % , respectively. CONCLUSIONS: PI stimulated ISB has good sensitivity , specificity and positive predictive value is comparable to stimulation with isoproterenol, which is the technique used, and is quick and simple. We recommend its routine use in the diagnosis of recurrent syncope of undetermined origin .